Liquid bridge: liquid metal bridging spherical BN largely enhances the thermal conductivity and mechanical properties of thermal interface materials. Issue 17 (7th April 2022) - Li, Junhong; Ma, Qiangqiang; Gao, Shan; Liang, Ting; Pang, Yunsong; Zeng, Xiangliang; Li, Ya-yun; Zeng, Xiaoliang; Sun, Rong; Ren, Linlin
Abstract : With the rapid development of advanced microelectronic equipment, thermal interface materials with high thermal conductivity and excellent mechanical properties have become an urgent need. Abstract : With the rapid development of advanced microelectronic equipment, thermal interface materials with high thermal conductivity and excellent mechanical properties have become an urgent need. Adding traditional thermally conductive fillers to polymers often leads to poor mechanical properties of thermal interface materials. In this paper, a liquid metal (LM) is used as an auxiliary filler to fill spherical boron nitride (SBN) polymer thermal interface materials. The liquid metal bridges the spherical boron nitride distributed in "islands", endowing the thermal interface materials with high thermal conductivity (4.00 W m −1 K −1, an increase of 227.66%), and excellent mechanical properties (elongation at break up to 198.96%, an increase of 81.24%). These experimental results show that the liquid metal, a flexible filler, can not only replace rigid fillers to reduce the contact thermal resistance between fillers through surface contact, but also improve the mechanical properties to a certain extent, breaking through the defects of traditional rigid fillers, and provides ideas for the future development of thermal interface materials.